Implementation of the STEM-PBL Approach in Online Chemistry Learning and its Impact on Students' Critical Thinking Skills - Siti Arisa; Debora Suryani Sitinjak (Universitas Pendidikan Ganesha, 2022)
Chemistry is a very important branch of science because it deals with phenomena that often occur in everyday life. In chemistry learning, students are invited to study the material and its changes. Chemistry learning is considered very abstract because it cannot be seen directly by the naked eye. It causes most high school students to think that chemistry is difficult—limitations of learning during the Covid-19 pandemic affected various abilities possessed by students. Students lack critical thinking skills, namely, the inability to analyze and provide solutions to simple problems. The purpose of this research is to develop students' critical thinking skills through the application of the STEM-PBL approach to online learning. This research uses a qualitative descriptive method with observation sheet instruments and test questions. STEM integrated into PBL is one of the solutions to improve students' critical thinking skills. The results of the application of STEM-PBL show an increase in students' critical thinking skills in solving everyday problems. Students can also design tools to solve problems and integrate various disciplines.